The God you're looking for - Hybels, Bill. (Nashville, Tenn. : Thomas Nelson Publishers, 1997)
Publisher description: Sooner or later almost everybody looks for God. High achievers who have done it all, low achievers who have no hope, the elderly who are running out of time, and the young who are running out of alternatives. But which God? Defined by Whom? Revealed where? Confirmed by how many? This book is about the God you are looking for. The God who revealed Himself, whose identity is not a mystery, and whose concern for you is not kept secret.
Introduction. Does He or doesn't He? -- Are you looking for a God . . . 1. Who knows it all? -- 2. Who is always there when you need Him? -- 3. Who is in control? -- 4. Who can laugh and cry with you? -- 5. Who is a refuge? -- 6. Who is righteous? -- 7. Who is always gracious? -- 8. Who is always committed to you? -- 9. Who always guides you? -- 10. Who always gives? -- 11. Who is always the same?
Includes bibliographical references (p. 201-203)
Keywords: God (Christianity)